STUDI EVALUASI DAN OPTIMASI TPA BANJARAN KABUPATEN PURBALINGGA - Rizki Bayu Sejati (Jurnal Teknik Lingkungan, 2012)
As another town in Indonesia, Purbalingga also use landfill as a place to dispose solid waste/ rubbish. The landfill that serving Purbalingga area is located in Desa Banjaran Kabupaten Purbalingga which has an area of 4,7 hectare.The landfill consist of two pile’s zone and at this time only one zone left that still can be operated. The main problem in Banjaran Landfill management is diminishing availability of area to dispose solid waste and there is not available an alternative area that can be used for landfill location which makes Purbalingga threatened do not have an area to dispose their solid waste/rubbish. Beside that, solid waste management in that landfill not meet the environmental quality standar and still operated with open dumping system. The aim of this study is to evaluate TPA Banjaran and provide some alternatives to optimize the TPA by changing the method of disposal to be Sanitary Landfill method, infrastructure improvements and additions that are not yet available and make TPA Banjaran can be used more effectively and more optimal. Based on the assessment of the feasibility using SK SNI T-11-1991-03, 1991 can be conclude that TPA Banjaran is decent with environmental control (value 513). In addition, this study found an alternative optimization of TPA Banjaran with site optimization and change the operational methods using the sanitary landfill method.